Safety of lixisenatide versus sulfonylurea added to basal insulin treatment in people with type 2 diabetes mellitus who elect to fast during Ramadan (LixiRam): An international, randomized, open-label trial. (April 2019) - Hassanein, Mohamed M.; Sahay, Rakesh; Hafidh, Khadija; Djaballah, Khier; Li, Haoyu; Azar, Sami; Shehadeh, Naim; Hanif, Wasim
Highlights: Lixisenatide + BI was beneficial and well tolerated as T2DM therapy during Ramadan. People with T2DM treated with lixisenatide + BI fasted safely during Ramadan. Lixisenatide + BI provided lower rates of any hypoglycemia vs SU + BI. Abstract: Aims: Adding lixisenatide to basal insulin (BI) instead of sulfonylurea (SU), versus continuing SU + BI was assessed in people with type 2 diabetes mellitus (T2DM) who intended to fast during Ramadan 2017. Methods: LixiRam (NCT02941367) was a phase 4, randomized, open-label, 12–22-week study in people with T2DM insufficiently controlled with SU + BI ± 1 oral anti-diabetic. Endpoints included the percentage of participants with ≥1 documented symptomatic hypoglycemia event (plasma glucose ≤70 mg/dL; primary endpoint) and any hypoglycemia during Ramadan fasting. Results: A numerically lower percentage of participants with lixisenatide + BI (3.3%, 3/91) versus SU + BI (8.9%, 8/90) had ≥1 documented symptomatic hypoglycemia event (intent-to-treat visit 4) during Ramadan fasting (OR: 0.34; 95% CI 0.09, 1.35; proportion difference −0.06, 95% CI −0.13, 0.01); the difference was statistically significant for the 'any hypoglycemia' category (lixisenatide + BI: 4.3%, 4/92; SU + BI: 17.4%, 16/92; OR: 0.22; 95% CI 0.07, 0.68; proportion difference −0.13, 95% CI −0.22, −0.04; intent-to-treat). No new treatment-emergent adverse events occurred. Conclusions: Compared with SU + BI, lixisenatide + BI provided lower rates of any hypoglycemia in people with T2DM during Ramadan fasting. Lixisenatide + BI therapy may be a suitable treatment option during fasting.